2000
DOI: 10.1103/physrevd.61.072003
|View full text |Cite
|
Sign up to set email alerts
|

Resonant structure ofτ3ππ0ντ

Abstract: The resonant structure of the four pion final state in the decay →3 0 has been analyzed using 4.27 million ϩ Ϫ pairs collected by the CLEO II experiment at the Cornell Electron Storage Ring. A partial wave analysis of the resonant structure of the →3 0 decay has been performed; the spectral decomposition of the four pion system is dominated by the and a 1 final states. The mass and width of the Ј resonance have been extracted from a fit to the → spectral function. We have searched for second class currents in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Expression for the integral I (3) ρ has a rather cumbersome form and contains a combination of terms with different powers of the form factor (up to the third power). It is constructed according to the Feynman rules coming from the Lagrangian (5). For calculation of the relevant quark loop integrals, we use the method described in Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression for the integral I (3) ρ has a rather cumbersome form and contains a combination of terms with different powers of the form factor (up to the third power). It is constructed according to the Feynman rules coming from the Lagrangian (5). For calculation of the relevant quark loop integrals, we use the method described in Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It is important to note that the studies in Refs. [4,5,10] concluded that the contribution of the ρ (1700) to the process is small. Following the results, this paper will neglect the contribution of the amplitude with intermediate ρ (1700) meson.…”
Section: Introductionmentioning
confidence: 97%
“…= 773.6(9) = 773.6(9) = 773.6(9) = 773.6(9) (15) 1376 (6) 1313 (15) 1311 (5) (12) 1718 (4) 1660 (9) 1658 (1) ρ → ωπ into the ρ decay width. In spirit of [48], we write the energy-dependent width as…”
Section: Dispersive Representationmentioning
confidence: 99%
“…So, strictly speaking the discontinuity of f ωπ (t) is not available for t > t + . On the other hand, the modulus of f ωπ (t) can be extracted from experimental data on e + e − → ωπ 0 process, measured in [19][20][21][22][23][24][25]. The connection between the cross section and the modulus [10,27] is, in our convention,…”
Section: Input In the Consistency Testmentioning
confidence: 99%
“…It is important to note that the dispersive analyses performed so far did not include experimental data on the form factor available in the scattering region, above the ωπ threshold. Measurements of the modulus from the reaction e + e − → ωπ 0 are reported in [19][20][21][22][23][24][25] (a set of such data is shown in Fig. 1, where we show for completeness also the modulus measured in the decay region t < t − , t − = (m ω − m π ) 2 ).…”
Section: Introductionmentioning
confidence: 99%